뇌사 판정 논의와 장기이식법의 개선방안 연구 - 이창규; 김주희; 김수동 (의생명과학과 법, 2022)
2000년부터 시행되고 있는「장기 등 이식에 관한 법률」은 뇌사 이식에 대해, 제공자의 생전 서면에 의한 제공의 의사 표시가 없더라도, 반대의 의사 표시가 없다면, 유족의 승낙을 얻어 뇌사판정이 가능하게 되었다. 장기의 기증에 관한 법률은 비교적 최근에 창설된 새로운 법률로, 의생명과학기술의 발달로 인해 시대적 논의 반영이 필요하다. 이에 따라 우리의「장기 등 이식에 관한 법률」의 문제점 도출과 개선을 위한 해외 법제의 현황과 입법 내용을 검토하는 것은 의미가 있다고 할 수 있다. 특히, 독일은 장기이식의 변화에 기초한 장기이식스캔들(Organspende-Skandal)이 있었고 이후 제도의 변화가 일어났다. 이를 기초로 독일 장기이식법의 장기 적출요건과 동의를 알아보고, 우리의 장기이식법에서의 몇 가지 개선점을 도출하였다. 첫째, 뇌사판정의 동의요건과 마찬가지로 제공자 본인이 동의하고 있음에도 불구하고, 유족의 거부 의사표시가 있다면 장기를 제공할 수 없는지에 대한 문제가 발생한다. 장기기증에 대하여 친족인 기증자의 사후 장기기증에 대하여 유족이 고유의 권리를 갖는다면, 당연히 거부권도 인정이 되지만 독일과 같이 가족 간 실질적인 유대나 긴밀한 교류를 전제로 하지 않는 우리나라의 친족 범위의 결정 방법은 친족에게 거부권을 인정하고 본인의 자기결정권을 경시하는 것은 문제가 될 것이다. 둘째, 장기 제공자와 수령인의 범위의 축소에 관한 사항이다. 장기이식법 제4조 제6호에 가족 또는 유족은 장기 등 기증자로부터의 장기 제공에 대해 승낙･거부의 의사 표시의 주체이다. 독일 장기이식법 제4조 제2항에서는 근친자(nächste Angehörige)로 하고, 근친자가 의사 결정의 권한을 가진 것은 제공자에게 사망 전 직전 2년 이내에 개인적 접촉을 취한 경우에만 주어져야 한다고 규정하고 있다. 즉, 근친자는 우선 배우자 또는 등록한 공동생활자(Lebenspartner), 자녀, 부모, 형제자매, 조부모이다. 또한, 근친자들 사이에 순위를 마련하고, 동등한 지위에 있는 근친자가 복수로 있는 경우에는 그중 한 명이 위의 사정을 충족하면 충분하다고 할 수 있다. The Act on Organ Transplantation makes it possible to judge brain death with the consent of the bereaved family, even if the donor does not express his/her intention to donate in writing before death, as long as the donor does not express his/her intention to the contrary. Legislation on long-term donations is a new area that was created relatively recently and is still developing with the development of medical and life science technology. It can be said that it is meaningful to examine the current state of overseas legal systems and the content of legislation in order to identify and improve the problems of laws related to transplantation of organs and other organs. In particular, Germany had an organ transplant scandal (Organspende-Skandal) based on changes in organ transplantation, followed by institutional changes. On this basis, we examined the long-term harvest requirements and consent of the German organ transplantation law and derived some improvements in our organ transplantation law. First, as with the consent requirements for determining brain death, there is a problem as to whether or not the bereaved family can refuse the donation despite the donor's consent. If the bereaved family has inherent rights to the long-term donation after the donor's death, the bereaved family will naturally have the right to veto the long-term donation. In the Korean method of determining the scope of relatives, which does not allow such relatives to have the right of veto, it would be a problem to neglect the person's right to self-determination. The second is the scope of long-term donors and recipients. Under the Organ Transplantation Law, family members or bereaved families are the subjects of consent or refusal of long-term donation of organs from donors. German long-term transplant law stipulates that close relatives and decision-making authority must only be given to the donor if they have had personal contact within the last two years prior to death. there is That is, close relatives are primarily spouses or registered Lebenspartners, children, parents, siblings and grandparents. In addition, if an arrangement is made among close relatives and there are multiple close relatives in the same position, it is sufficient if one of them satisfies the above circumstances. KCI Citation Count: 0